Faktor-Faktor yang Mempengaruhi Perkembangan UMKM di Kota Banda Aceh - Mimiasri; Nasrul Hadi; Aiyub Saputra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2022)
Micro, small and medium enterprises (MSMEs) play an important and strategic role and play a key role in terms of employment, poverty alleviation and economic growth in the region. In Banda Aceh, the existence of MSMEs is very important as a means of livelihood for the community. SMEs have become an alternative provider of employment opportunities in Banda Aceh City, especially as unemployment numbers are rising in Banda Aceh City after oil and gas depletion and slow industrial growth. The survey included a sample of 100 of his MSME entrepreneurs spread across Banda Aceh. Each subdistrict was selected by MSME entrepreneurs using a targeted sampling method. Depiction of MSME performance situation was descriptively analyzed by describing various aspects such as MSME development, MSME age, and number of employees.